Comparison of 2 proposed MLVA protocols for subtyping non-O157:H7 verotoxigenic Escherichia coli - González, Juliana (2013)
Multiple locus variable number tandem repeats (VNTRs) analysis (MLVA) has become a reliable tool, able to establish genetic relationships for epidemiological surveillance and molecular subtyping of pathogens such as verotoxigenic Escherichia coli (VTEC). This emerging pathogen whose primary reservoir is the cattle causes severe disease in humans, such as hemorrhagic colitis and hemolytic uremic syndrome. With the aim of comparing a recently proposed MLVA assay with that used routinely in our laboratory, we analyzed a set of VTEC isolates (n = 72) obtained from meat using both assays. All samples could be typed by the new MLVA assay, and an increase in the number of distinct profiles (31–43) was observed. However, intraserotype resolution was not significantly enhanced; thus, the incorporation of more VNTR loci is still needed to achieve a greater discrimination among non-O157:H7 serotypes.